Management of Excellence in Higher Education According to the European Model of Excellence: A Study Case of College of Education - Skikda - Zerzar Alayachi; Hamza Ben Oarida (University of Science and Technology, Yemen, 2020)
This study aimed to identify the degree of application of excellence management elements according to the European Model of Excellence (EFQM) at the College of Education of Skikda. To achieve the objectives of the study, the descriptive analytical method was used on 95 fulltime professors, selected by the complete census method, participated in the study. To collect data, a questionnaire was used after checking its validity and reliability by calculating the coefficients of correlation and alpha Cronbach where the latter was 0.964. The results showed that the level of application of the European model of excellence in the faculty of education was 71%. It was recommended therefore that more attention and focus should be made to the European model of excellence management by the college administration. The importance and benefits of adopting this recommendation should be made clear to the ministry as well as to other stakeholders.